Antecedents of User Trust in MITA Chatbot: A Study of Bank Mandiri Digital Services - Mariska Nanda Ranelita; Arif Hartono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Digital transformation has driven financial institutions to adopt chatbot technology to enhance service efficiency and customer satisfaction. This study aims to analyze the influence of service quality, interface design, perceived risk, and structural assurance on user trust in chatbots, focusing on the MITA WhatsApp Business chatbot of Bank Mandiri. A quantitative approach was employed, involving 262 respondents selected through purposive sampling. The participants were Bank Mandiri customers who had used the MITA chatbot service. Data were collected through questionnaires using a five-point Likert scale and analyzed using SPSS and Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS software. The hypothesis testing results indicate that service quality and interface design significantly impact user trust in the chatbot. In contrast, perceived risk and structural assurance do not significantly influence user trust. Furthermore, chatbot trust positively affected behavioral intention and user satisfaction. This study is expected to provide insights for marketing managers in developing strategies to foster user trust in chatbot services within the banking sector and understand its implications for user behavior and future digital service development.